2020
DOI: 10.1182/blood.2019003267
|View full text |Cite
|
Sign up to set email alerts
|

CDK6 is an essential direct target of NUP98 fusion proteins in acute myeloid leukemia

Abstract: Fusion proteins involving Nucleoporin 98 (NUP98) are recurrently found in acute myeloid leukemia (AML) and are associated with poor prognosis. Lack of mechanistic insight into NUP98-fusion-dependent oncogenic transformation has so far precluded the development of rational targeted therapies. We reasoned that different NUP98-fusion proteins deregulate a common set of transcriptional targets that might be exploitable for therapy. To decipher transcriptional programs controlled by diverse NUP98-fusion proteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 49 publications
2
52
1
Order By: Relevance
“…Further evaluation both ex vivo in patient-derived AML cells and in vivo in immunodeficient mice transplanted with RUNX1/ETO-expressing AML cells demonstrated a high sensitivity of this AML subtype to palbociclib inhibition. Interestingly, similar findings have also been reported for AMLs expressing FLT3-ITD or another leukemic fusion protein NUP98/NSD1 [ 88 , 89 ]. Inhibition of CDK4/6 is cytostatic; ongoing research, thus, aims to identify novel drug combinations with, e.g., MTOR inhibitors or components of current chemotherapy such as cytarabine for the elimination of leukemic cells [ 90 , 91 ].…”
Section: Therapeutic Targeting Of Runx1/etosupporting
confidence: 81%
“…Further evaluation both ex vivo in patient-derived AML cells and in vivo in immunodeficient mice transplanted with RUNX1/ETO-expressing AML cells demonstrated a high sensitivity of this AML subtype to palbociclib inhibition. Interestingly, similar findings have also been reported for AMLs expressing FLT3-ITD or another leukemic fusion protein NUP98/NSD1 [ 88 , 89 ]. Inhibition of CDK4/6 is cytostatic; ongoing research, thus, aims to identify novel drug combinations with, e.g., MTOR inhibitors or components of current chemotherapy such as cytarabine for the elimination of leukemic cells [ 90 , 91 ].…”
Section: Therapeutic Targeting Of Runx1/etosupporting
confidence: 81%
“…CDK6 also plays a crucial role in malignant hematopoietic tumors. It is not only required for maintenance of NUP98-fusion AML but also could act an important role in MLL (KMT2A) fusions-mediated myeloid leukemogenesis ( Schmoellerl et al, 2020 ). Some AML patients with FLT3-ITD mutation failed to induce a persistent response via FLT3 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the corresponding gene loci are bound by leukaemic fusion proteins and may, thus, be directly controlled by them. For instance, the CDK6 and CCND3 loci are direct target genes of MLL/AF4, the most frequent fusion protein found in infant leukaemia, and several NUP98 fusion proteins drive CDK6 transcription by binding to its promoter [5,7]. Thus, promotion of G1 cell cycle phase progression by activating CDK6 expression is a common theme for leukaemic fusion proteins (Fig.…”
Section: Therapeutic Targeting Of the Cell Cycle In Amlmentioning
confidence: 99%
“…Recently, a third class has been suggested that separates mutated epigenetic modifiers and readers from class 2. However, more recent investigations of transcriptional networks underlying the leukaemic phenotypes have blurred this clear distinction with type 2 members also promoting proliferation by controlling growth factor and cell cycle genes such as FLT3, CDK6 or CCND2 [5][6][7]. Since pre-leukaemic and leukaemic self-renewal is dependent on cells cycle progression, it is not really surprising that class 2 mutations also drive proliferation as part of their programme.…”
Section: Introductionmentioning
confidence: 99%